Comparison of cytotoxicity test models for evaluating resin-based composites. (April 2017) - Lim, SM; Yap, AUJ; Loo, CSL; Ng, J; Goh, CY; Hong, CHL; Toh, WS
Objectives: This study compared different cytotoxicity test models for evaluating resin-based composites (RBCs) and assessed the biocompatibility of standard and bulk-fill RBCs. Methods: A standard (spectrum TPH) and a bulk-fill (smart dentin replacement (SDR)) RBC were selected. Disc-shaped specimens (7 mm diameter) of 2 and 4 mm thickness were polymerized for 20 s with a LED curing light of 700 mW/cm 2 irradiance. The specimens ( n = 5) were subjected to micro-hardness testing and three cytotoxicity test models (direct contact, indirect contact and extract tests) with the established L-929 cell line. Hardness ratios of top and bottom surfaces of specimens were computed to assess the effectiveness of cure. For the direct and indirect contact tests, the cells were stained and zones of inhibition were analyzed after material contact for 24 h. For the extract test, cells were exposed to extracts for 24 h, and cell viability was measured. Data was analyzed using analysis of variance/Scheffe's post hoc test and Pearson's correlation ( p < 0.05). Results: The lowest mean hardness ratio and highest cytotoxicity were observed for TPH at 4 mm. At 4-mm thickness, SDR was found to be biocompatible with all three models. Correlations between hardness ratio and cell viability ranged from r = 0.89–0.96 for the various tests. A significant correlation ( r = 0.97) was also observed between the three test models. Conclusion: Our data indicated consistency between direct contact, indirect contact and extract test models for cytotoxicity testing of RBCs. Bulk placement and curing at 4 mm for the bulk-fill RBC evaluated did not result in undue cytotoxicity.